Using Bionics to Restore Sensation to Reconstructed Breasts - Lindau, Stacy T.; Bensmaia, Sliman J. (Frontiers in Neurorobotics, 2020)
Mastectomy often leads to a complete desensitization of the chest, which in turn can give rise to sexual dysfunction and to disembodiment of the breasts. One approach to avoiding or reversing the sensory consequences of mastectomy is to invoke technology that has been developed for the restoration of sensation in bionic hands. Specifically, sensors imbedded under the skin of the nipple-areolar complex can be used to detect touches. The output of the sensors then drives electrical stimulation of the residual intercostal nerves, delivered through chronically implanted electrode arrays, thereby eliciting tactile sensations experienced on the nipple-areolar complex. Women equipped with these bionic breasts will feel whole again and their ability to experience the squeeze of an embrace or the sensual touch of a lover will be restored.